Adaptation and validation of the Patient Health Questionnaire-9 to evaluate major depression in a primary care sample in Latvia. (17th February 2018) - Vrublevska, Jelena; Trapencieris, Marcis; Rancans, Elmars
Abstract: Background: Depression is one of the most common mental disorders in primary care settings and is often underdiagnosed and undertreated by general practitioners (GPs). To date, no depression screening instruments have been validated for use in primary care settings in Latvia. The aim of this study was to establish the validity and cutoff score of the Patient Health Questionnaire-9 (PHQ-9) among primary care patients in Latvia. Materials and methods: During a one-week period, all consecutive patients aged 18 years or older visiting their GP of health concerns at 6 primary care settings were invited to complete the PHQ-9 questionnaire in their native language (Latvian or Russian). Criterion validity was assessed against the Mini International Neuropsychiatric Interview (M.I.N.I.), which was conducted over the telephone by a psychiatrist less than 2 weeks after a primary care physician visit. Results: In total, 324 patients were evaluated using the PHQ-9, 272 of whom agreed to be interviewed with the M.I.N.I. Overall, the PHQ-9 items showed good internal (Cronbach's alpha 0.84) reliability. A cutoff score of 10 was established for the PHQ-9 (sensitivity 86.49%, specificity 89.36%), correctly classifying 86.4% of patients with current depression. Conclusions: The PHQ-9 appears to be a reliable and valid instrument that can be used to diagnose major depression among Latvian and Russian speaking adults at the primary care level.